Corrosion-resistant concrete and preparation method thereof
By using modified potassium powder in concrete, combined with the modification technology of latex emulsion and nano -zinc oxide, the problem of lack of compression strength and corrosion resistance of concrete, which significantly improves its performance, making it more suitable for complexity Engineering application.
Patent Information
- Application Number
- CN202411602005.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-28
AI Technical Summary
At this stage, concrete still cannot meet the high requirements of the market in terms of compressive strength and corrosion resistance.
By introducing modified potassium long stone powder, specifically, the potassium powder is mixed with modified agents such as latex emulsion and nano -zinc oxide to prepare a corrosion -resistant concrete. This modified potassium powder has enhanced the combination of latex and nano -zinc oxide, which enhances its combination with other raw materials and improves the stability of the internal structure of concrete.
It significantly improves the compressive strength and corrosion resistance of corrosive concrete, making it better meet the high requirements of market resistance and corrosion resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to corrosion-resistant concrete and a preparation method thereof. Background Art
[0002] Concrete is an engineering composite material made of cementitious materials, fine aggregate materials, water and other admixtures mixed in a certain proportion. It has many excellent properties and a wide range of applications. Concrete is most widely used in building structures. It can be used to build various building components such as floors, walls, columns and foundations. Concrete can withstand large water flows, impacts and geological changes, and is also an indispensable material in infrastructure construction.
[0003] Although concrete has excellent performance, it also has shortcomings in practical applications. With the increasing research and application of concrete, the market has put forward higher requirements for the compressive strength and corrosion resistance of concrete. Although the current concrete has certain compressive strength and corrosion resistance, it still cannot meet people's needs. Therefore, improving the compressive strength and corrosion resistance of concrete is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The invention provides corrosion-resistant concrete and a preparation method thereof, which solves the problems of poor compressive strength and poor corrosion resistance of concrete in the related art.
[0005] The technical solution of the present invention is as follows: The present invention provides a corrosion-resistant concrete, the raw materials of which include the following components in parts by weight: 35-45 parts of cement, 3-8 parts of fly ash, 12-24 parts of medium sand, 10-20 parts of crushed stone, 15-25 parts of modified potassium feldspar powder, 1-3 parts of water reducer, 1-3 parts of expansion agent, and 15 parts of water; The raw materials of the modified potassium feldspar powder include potassium feldspar powder and a modifier; The modifier includes a latex-type emulsion; The weight ratio of the potassium feldspar powder to the modifier is 20:0.5-7.
[0006] As a further technical solution, the weight ratio of the potassium feldspar powder to the modifier is 20:1~6.
[0007] When the weight ratio of potassium feldspar powder and modifier is 20:1~6, the compressive strength and corrosion resistance of corrosion-resistant concrete can be further improved.
[0008] As a further technical solution, the modifier is a latex emulsion.
[0009] As a further technical solution, the latex emulsion includes one or both of polyvinyl acetate emulsion and styrene acrylic emulsion, preferably polyvinyl acetate emulsion.
[0010] As a further technical solution, the preparation method of the modified potassium feldspar powder comprises the following steps: uniformly mixing the latex emulsion and the potassium feldspar powder, solidifying, and grinding to obtain the modified potassium feldspar powder.
[0011] As a further technical solution, the modifier also includes nano zinc oxide.
[0012] The inventors found that when nano zinc oxide is introduced into the modifier, the compressive strength and corrosion resistance of the corrosion-resistant concrete can be further improved by modifying the potassium feldspar powder with nano zinc oxide and latex emulsion. The reason may be that the addition of nano zinc oxide can promote the close combination of latex emulsion and potassium feldspar powder, so that the modification effect of potassium feldspar powder is optimal, so that the potassium feldspar powder can be more effectively filled into the pores of the internal structure of the concrete, further improving the compressive strength and corrosion resistance of the corrosion-resistant concrete.
[0013] As a further technical solution, the weight ratio of the latex emulsion to the nano zinc oxide is 3:1-2.
[0014] When the weight ratio of latex emulsion and nano zinc oxide is 3:1~2, the compressive strength and corrosion resistance of corrosion-resistant concrete can be further improved by reasonably adjusting the weight ratio of the two.
[0015] As a further technical solution, the particle size of the potassium feldspar powder is 50-100 μm; the particle size of the nano zinc oxide is 20-50 nm.
[0016] As a further technical solution, the preparation method of the modified potassium feldspar powder comprises the following steps: A1, mixing the potassium feldspar powder and the nano zinc oxide uniformly to obtain a mixture; A2. Evenly mix the mixture and the latex emulsion, solidify, and grind to obtain the modified potassium feldspar powder.
[0017] As a further technical solution, the crushed stone is one or more of basalt crushed stone, granite crushed stone, and dolomite crushed stone.
[0018] As a further technical solution, the medium sand is one or more of quartz sand, machine-made sand, and basalt sand.
[0019] As a further technical solution, the water reducer is one or more of polycarboxylic acid water reducer, naphthalene water reducer and lignin sulfonate.
[0020] As a further technical solution, the expansion agent is one or both of a calcium sulfoaluminate expansion agent and a calcium oxide expansion agent.
[0021] As a further technical solution, the particle size of the crushed stone is 2~15mm.
[0022] As a further technical solution, the particle size of the fly ash is 30-100 μm.
[0023] As a further technical solution, the particle size of the medium sand is 0.25~0.5mm.
[0024] The present invention also provides a method for preparing the corrosion-resistant concrete, comprising the following steps: evenly mixing the fly ash, medium sand, crushed stone and modified potassium feldspar powder, adding the remaining raw materials, mixing and stirring, and obtaining the corrosion-resistant concrete.
[0025] The working principle and beneficial effects of the present invention are: In the present invention, the raw materials of the corrosion-resistant concrete include cement, fly ash, medium sand, crushed stone, and modified potassium feldspar powder. Through the effective coordination between the raw materials, corrosion-resistant concrete with a stable internal structure can be prepared, so that the concrete has high compressive strength and good corrosion resistance. Among them, the modified potassium feldspar powder is obtained by modifying potassium feldspar powder with a latex emulsion. The potassium feldspar powder is modified by the latex emulsion, which enhances the combination of potassium feldspar powder and other raw materials, realizes the close filling between particles, and thus significantly improves the compressive strength and corrosion resistance of the corrosion-resistant concrete. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In the following embodiments and comparative examples, cement is ordinary Portland cement, model PO42.5; the particle size of fly ash is 44 μm; medium sand is quartz sand, with a particle size of 0.5 mm; crushed stone is basalt crushed stone, with a particle size of 5 mm; the particle size of potassium feldspar powder is 74 μm; the particle size of nano zinc oxide is 30 nm; the water reducer is sodium lignin sulfonate, model 85A; the expansion agent is calcium sulfoaluminate expansion agent, specifically UEA expansion agent, model UEA-A; the model of polyvinyl acetate emulsion is SD-40; the model of styrene acrylic emulsion is 910A.
[0028] Example 1 A corrosion-resistant concrete, the raw materials include the following components in parts by weight: 35 parts of cement, 3 parts of fly ash, 12 parts of medium sand, 10 parts of crushed stone, 15 parts of modified potassium feldspar powder, 1 part of sodium lignin sulfonate, 1 part of UEA expansion agent, 15 parts of water; The preparation method of modified potassium feldspar powder comprises the following steps: uniformly mixing 0.375 parts of styrene acrylic emulsion and 15 parts of potassium feldspar powder, solidifying, and grinding to obtain modified potassium feldspar powder; The preparation method of corrosion-resistant concrete comprises the following steps: after uniformly mixing the fly ash, medium sand, crushed stone and modified potassium feldspar powder, adding other raw materials, mixing and stirring, corrosion-resistant concrete can be obtained.
[0029] Example 2 A corrosion-resistant concrete, the raw materials include the following components in parts by weight: 40 parts of cement, 5 parts of fly ash, 18 parts of medium sand, 15 parts of crushed stone, 20 parts of modified potassium feldspar powder, 2 parts of sodium lignin sulfonate, 2 parts of UEA expansion agent, 15 parts of water; The preparation method of modified potassium feldspar powder comprises the following steps: uniformly mixing 0.5 parts of polyvinyl acetate emulsion and 20 parts of potassium feldspar powder, solidifying, and grinding to obtain modified potassium feldspar powder; The preparation method of corrosion-resistant concrete comprises the following steps: after uniformly mixing the fly ash, medium sand, crushed stone and modified potassium feldspar powder, adding other raw materials, mixing and stirring, corrosion-resistant concrete can be obtained.
[0030] Example 3 A corrosion-resistant concrete, the raw materials include the following components in parts by weight: 45 parts of cement, 8 parts of fly ash, 24 parts of medium sand, 20 parts of crushed stone, 25 parts of modified potassium feldspar powder, 3 parts of sodium lignin sulfonate, 3 parts of UEA expansion agent, 15 parts of water; The preparation method of modified potassium feldspar powder comprises the following steps: uniformly mixing 8.75 parts of styrene acrylic emulsion and 25 parts of potassium feldspar powder, solidifying, and grinding to obtain modified potassium feldspar powder; The preparation method of corrosion-resistant concrete comprises the following steps: after uniformly mixing the fly ash, medium sand, crushed stone and modified potassium feldspar powder, adding other raw materials, mixing and stirring, corrosion-resistant concrete can be obtained.
[0031] Example 4 The only difference between this embodiment and embodiment 2 is that, in this embodiment, when preparing the modified potassium feldspar powder, the weight parts of potassium feldspar powder are 20 parts, and the weight parts of polyvinyl acetate emulsion are 7 parts.
[0032] Example 5 The only difference between this embodiment and embodiment 2 is that, in this embodiment, when preparing the modified potassium feldspar powder, the weight part of potassium feldspar powder is 20 parts, and the weight part of polyvinyl acetate emulsion is 1 part.
[0033] Example 6 The only difference between this embodiment and embodiment 2 is that, in this embodiment, when preparing the modified potassium feldspar powder, the weight parts of potassium feldspar powder are 20 parts, and the weight parts of polyvinyl acetate emulsion are 6 parts.
[0034] Example 7 The difference between this embodiment and embodiment 6 is that, in this embodiment, the raw material of the modified potassium feldspar powder further includes nano zinc oxide, and the preparation method of the modified potassium feldspar powder includes the following steps: A1. Mix 20 parts of potassium feldspar powder and 1 part of nano zinc oxide to obtain a mixture; A2. The mixture and 6 parts of polyvinyl acetate emulsion are mixed evenly, solidified, and ground to obtain modified potassium feldspar powder.
[0035] Example 8 The only difference between this embodiment and embodiment 7 is that in this embodiment, when preparing the modified potassium feldspar powder, the weight parts of potassium feldspar powder are 20 parts, the weight parts of polyvinyl acetate emulsion are 6 parts, and the weight parts of nano zinc oxide are 5 parts.
[0036] Example 9 The only difference between this embodiment and embodiment 7 is that in this embodiment, the weight parts of potassium feldspar powder are 20 parts, the weight parts of polyvinyl acetate emulsion are 6 parts, and the weight parts of nano zinc oxide are 2 parts.
[0037] Example 10 The only difference between this embodiment and embodiment 7 is that in this embodiment, the weight parts of potassium feldspar powder are 20 parts, the weight parts of polyvinyl acetate emulsion are 6 parts, and the weight parts of nano zinc oxide are 4 parts.
[0038] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, 15 parts of modified potassium feldspar powder are replaced by an equal amount of potassium feldspar powder.
[0039] Comparative Example 2 A corrosion-resistant concrete, the raw materials include the following components in parts by weight: 35 parts of cement, 3 parts of fly ash, 12 parts of medium sand, 10 parts of crushed stone, 15 parts of potassium feldspar powder, 0.375 parts of polyvinyl acetate emulsion, 1 part of sodium lignin sulfonate, 1 part of UEA expansion agent, 15 parts of water; The preparation method of corrosion-resistant concrete comprises the following steps: evenly mixing the fly ash, medium sand, crushed stone, potassium feldspar powder and polyvinyl acetate emulsion, adding other raw materials, mixing and stirring, and thus obtaining corrosion-resistant concrete.
[0040] The corrosion-resistant concrete prepared in Examples 1 to 10 and Comparative Examples 1 to 2 was cured according to the curing method in GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the curing age was 28 days. The following performance tests were performed on the cured corrosion-resistant concrete: ① Compressive strength test: The compressive strength test of the corrosion-resistant concrete specimens was carried out according to the test method of GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". During the test, the loading speed was 0.5MPa / s, the specimens were cubic specimens with a side length of 150mm, each group of specimens consisted of 3 pieces, and the test results were the average of the test results of the 3 specimens; ②Corrosion resistance test: After the compressive strength of the corrosion-resistant concrete specimens after curing is tested according to the above-mentioned compressive strength test method, the corrosion-resistant concrete specimens are subjected to a sulfate corrosion test according to the test method in GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and the compressive strength corrosion resistance coefficient is calculated according to the following formula: compressive strength corrosion resistance coefficient (%) = compressive strength after sulfate corrosion test / compressive strength without sulfate corrosion test × 100%, wherein, during the sulfate corrosion test, the number of dry-wet cycles is 15 times, the specimen is a cubic specimen with a side length of 100 mm, each group of specimens consists of 3 specimens, and the test result is the average of the test results of the 3 specimens.
[0041] The results are shown in Table 1 below: Table 1 Compressive strength and corrosion resistance test results of Examples 1 to 10 and Comparative Examples 1 to 2
[0042] Compared with comparative examples 1 and 2, the compressive strength and compressive strength corrosion resistance coefficient of Example 1 are significantly improved, indicating that the compressive strength and corrosion resistance of corrosion-resistant concrete can be improved by modifying potassium feldspar powder using latex emulsion.
[0043] Compared with Examples 2 and 4, the compressive strength and compressive strength corrosion resistance coefficient of Examples 5 to 6 are improved, indicating that when the weight ratio of potassium feldspar powder to modifier is 20:1 to 6, the compressive strength and corrosion resistance of the corrosion-resistant concrete can be further improved.
[0044] Compared with Example 6, the compressive strength and compressive strength corrosion resistance coefficient of Examples 7 to 10 are improved, indicating that when nano zinc oxide is introduced into the modifier, the compressive strength and corrosion resistance of the corrosion-resistant concrete can be further improved by jointly modifying the potassium feldspar powder with nano zinc oxide and latex emulsion.
[0045] Compared with Examples 7 to 8, the compressive strength and compressive strength corrosion resistance coefficient of Examples 9 to 10 are improved, indicating that when the weight ratio of latex emulsion and nano zinc oxide is 3:1 to 2, the compressive strength and corrosion resistance of corrosion-resistant concrete can be further improved by reasonably regulating the weight ratio of the two.
[0046] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant concrete, characterized in that: The raw materials include the following components in parts by weight: 35-45 parts of cement, 3-8 parts of fly ash, 12-24 parts of medium sand, 10-20 parts of crushed stone, 15-25 parts of modified potassium feldspar powder, 1-3 parts of water reducer, 1-3 parts of expansion agent, and 15 parts of water; The raw materials of the modified potassium feldspar powder include potassium feldspar powder and a modifier; The modifier includes a latex-type emulsion; The weight ratio of the potassium feldspar powder to the modifier is 20:0.5-7.
2. The corrosion-resistant concrete according to claim 1, characterized in that: The weight ratio of the potassium feldspar powder to the modifier is 20:1-6.
3. The corrosion-resistant concrete according to claim 1, characterized in that: The latex emulsion includes one or both of polyvinyl acetate emulsion and styrene acrylic emulsion.
4. The corrosion-resistant concrete according to claim 1, characterized in that: The preparation method of the modified potassium feldspar powder comprises the following steps: uniformly mixing the latex emulsion and the potassium feldspar powder, solidifying, and grinding to obtain the modified potassium feldspar powder.
5. The corrosion-resistant concrete according to claim 1, characterized in that: The modifier also includes nano zinc oxide.
6. The corrosion-resistant concrete according to claim 5, characterized in that: The weight ratio of the latex emulsion to the nano zinc oxide is 3:1-2.
7. The corrosion-resistant concrete according to claim 5, characterized in that: The preparation method of the modified potassium feldspar powder comprises the following steps: A1, mixing the potassium feldspar powder and the nano zinc oxide uniformly to obtain a mixture; A2. Evenly mix the mixture and the latex emulsion, solidify, and grind to obtain the modified potassium feldspar powder.
8. The corrosion-resistant concrete according to claim 1, characterized in that: The crushed stone is one or more of basalt crushed stone, granite crushed stone, and dolomite crushed stone; and / or The medium sand is one or more of quartz sand, machine-made sand, and basalt sand; and / or The water reducer is one or more of polycarboxylic acid water reducer, naphthalene water reducer and lignin sulfonate.
9. The corrosion-resistant concrete according to claim 1, characterized in that: The expansion agent is one or both of a calcium sulfoaluminate expansion agent and a calcium oxide expansion agent.
10. The method for preparing corrosion-resistant concrete according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: evenly mixing the fly ash, medium sand, crushed stone and modified potassium feldspar powder, adding other raw materials, mixing and stirring, and thus obtaining the corrosion-resistant concrete.